Peran Pendidikan Pancasila terhadap Digitalisasi Pendidikan di Indonesia - Annisa Humaira Putri; Dwi Cahyo Mulyo Nugroho; Muhamad Hata; Muhamad Zaki Fadilah; Septrian, Raden Farhan Rizki; Siti Hajar Lutfiah; Yayang Furi Furnamasari (Indo-MathEdu Intellectuals Journal, 2024)
The digitalization of education in Indonesia, which is characterized by high levels of internet usage, has positive impacts such as wider access to information and flexible learning. However, it also presents challenges in terms of learning concentration and responsible use of technology. Pancasila education plays an important role in this context by integrating the nation's noble values in the use of digital technology. This article explores how the ideology of Pancasila can direct digital education to be in line with national values, as well as strengthen the character of students. This article uses a literature study method conducted through data collection from research journal articles. This data collection method is with the help of the internet to obtain references to previous research journals. The main source of article data in this study is articles published through google scholar. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusions. The results show that Pancasila has great potential in shaping national identity and guiding the younger generation in facing the digital era. Pancasila is not only the basis of the state, but also a moral and ethical guide in utilizing technology for positive and constructive purposes. Thus, Pancasila education must be used as a foundation in the development of digital education in Indonesia to create a society of faith, piety, and noble personality